Academic stress and life satisfaction as social sustainability among university students - Balan Rathakrishnan; Soon Singh Bikar Singh; Azizi Yahaya; Mohammad Rahim Kamaluddin; Fauziah Ibrahim; Zaizul Ab Rahman (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study was conducted to determine the relationship between academic stress and life satisfaction among university students in Sabah, Malaysia. A total of 400 students were selected as respondents and data were collected using questionnaires. Academic stress was measured using the Perception of Academic Stress Scale (PAS), which has four subscales: i) Performance stress; ii) Workload perception of workload and examinations; iii) Academic self-perception; and iv) Time constraints. Meanwhile, the Satisfaction with Life Scale was used to study student’s life satisfaction. The data obtained were analyzed using Pearson correlation and t-test. The results showed that performance stress is negatively associated with life satisfaction, while academic self-perception is positively associated with life satisfaction. The result also showed that perception of workload and examinations and time constraints not associated with life satisfaction. All in all, academic self-perception and performance stress have an association with life satisfaction.